Does Consensus Imply Accuracy in Accounting Studies of Decision Making? - Ashton, Alison Hubbard (The Accounting Review, 1985)
[The empirical relationship between consensus and accuracy is examined in two prediction tasks of interest to accountants-a managerial accounting task and an auditing task. The relationship between these two attributes is particularly important in auditing contexts in which consensus is sometimes accepted as a practical goal. The results of this study indicate a consistent, highly positive relationship between consensus and accuracy. The mean Pearson (Spearman) correlation between the two attributes was.84 (.82) across (1) the two tasks, which featured both continuous and dichotomous outcomes and which were performed by different sets of experts, (2) both individual and pairwise measures of subjects' consensus and accuracy, and (3) both correlational and absolute measures of performance in the managerial accounting task.]